Zinc and Iron Concentrations in Blood and Organs of Di-(2ethylhexyl)phthalate (DEHP)-treated Rats - Shigeru Suna; Fumihiko Jitsunari (Asian Journal of Medicine & Health Sciences, 2024)
Oral administration of di(2-ethylhexyl)phthalate (DEHP) to rats is known to induce testicular atrophy and hepatomegaly. This is thought to be the result of increased oxidative stress due to induction of peroxisomal enzymes by mono(2-ethylhexyl)phthalate (MEHP), a metabolite of DEHP. Therefore, changes in the metal content of organs are predicted. Therefore, an experiment was conducted in which rats were fed a diet containing DEHP for two weeks. Metal concentrations in blood and organs were measured, with a focus on zinc and iron. Results are as follows: DEHP treated rats had lower body weight and zinc concentrations in blood, liver, kidney, and testicular tissue, and higher iron concentrations in the liver compared to controls. These changes also correlated with plasma MEHP concentrations, suggesting MEHP-mediated oxidative stressinduced tissue damage and thyroid hormone disruption